On the issue countent and scope of the notion of the personality of juvenile violent lucrative delinquent - Маршуба, М. О. (Theory and practice of jurisprudence, 2016)
The contents and the specific scope of the notion “the personality of juvenile violent lucrative delinquent» from the position of system analysis is reveals in this scientific article. In addition, the article is examination of the different points of view with regard to the structural elements, which formed the basis of criminological study of such person.